Diseño y construcción de una trituradora para el aprovechamiento de residuos sólidos orgánicos en la florícola adelflowers. - Guzmán Guzmán, Juan Alex (2018)
This project had as its main objective the design and implementation of a rock crusher of solid waste organic, the same that was implemented in the flower "ADELFLOWERS", located in the province of Pichincha - Cayambe - Parish Juan Montalvo - neighborhoods of Santa Isabel, is an initiative that seeks to take advantage of these waste as compost. The shredding machine is a computer that allows you to reduce the size of the waste by means of mechanical forces to which they are subjected to the stems of the flowers, so as to reduce the time on the elaboration of compos. The machine is equipped with mechanical parts, and electrical, being the mechanical parts, the structure in general of the machine as are: the feed hopper and download, the transmission system of power and the system of crushing that consists of (steering wheel, knives, hammers, sweepers and axis), the electrical part is located in the structure of the machine and has pushbuttons, switch, pilot lights and relay thermo magnetic. Crushing given through a mechanical process and electrical, where the power and speed provided by the electric motor are transmitted by means of the transmission toward the main axis that contains the steering wheel with the knives and hammers, the same that are responsible for reduced in size to the waste. The results obtained through the tests were expected to have a size of organic solid waste of 1 to 3 cm to be optimal for the elaboration of compost. Switches Thermo Magnetic protect the electrical system of power and control, in order to safeguard the proper functioning of the equipment and the security of the people.